Pathobiology of cancer chemotherapy-induced peripheral neuropathy (CIPN) - Han, Yaqin; Smith, Maree T. (Frontiers in Pharmacology, 2013)
Chemotherapy induced peripheral neuropathy (CIPN) is a type of neuropathic pain that is a major dose-limiting side-effect of potentially curative cancer chemotherapy treatment regimens that develops in a ‘stocking and glove’ distribution. When pain is severe, a change to less effective chemotherapy agents may be required, or patients may choose to discontinue treatment. Medications used to alleviate CIPN often lack efficacy and/or have unacceptable side-effects. Hence the unmet medical need for novel analgesics for relief of this painful condition has driven establishment of rodent models of CIPN. New insights on the pathobiology of CIPN gained using these models are discussed in this review. These include mitochondrial dysfunction and oxidative stress that are implicated as key mechanisms in the development of CIPN. Associated structural changes in peripheral nerves include neuronopathy, axonopathy and/or myelinopathy, especially intra-epidermal nerve fiber (IENF) degeneration. In patients with CIPN, loss of heat sensitivity is a hallmark symptom due to preferential damage to myelinated primary afferent sensory nerve fibers in the presence or absence of demyelination. The pathobiology of CIPN is complex as cancer chemotherapy treatment regimens frequently involve drug combinations. Adding to this complexity, there are also subtle differences in the pathobiological consequences of commonly used cancer chemotherapy drugs, viz platinum compounds, taxanes, vincristine, bortezomib, thalidomide and ixabepilone, on peripheral nerves.